Comparative Evaluation of Hard-Tissue and Soft-Tissue Changes following Fixed Functional Appliance Treatment in a Skeletal Class II Malocclusion Using Forsus and PowerScope - Shetty, Prajwal; Shetty, Mukul; Chalapati, Maitreyi; Kori, Chaitra; Soans, Crystal Runa; S., Murali P. (Journal of Health and Allied Sciences NU, 2021)
Introduction The purpose of this study was to evaluate and compare the skeletal, dentoalveolar and soft-tissue effects of 2 fixed functional appliance; Forsus Fatigue Resistance Device (FFRD) and PowerScope appliance in treating patients with skeletal class II division 1 malocclusion.Materials and Methods This comparative prospective two-group study included 20 patients with a mean age of 11.2 ± 1.6 years with skeletal class II malocclusion with retrognathic mandible. One group was treated with FFRD, and second group was treated with PowerScope appliance. Lateral cephalograms were evaluated at T1 (pre-functional appliance treatment)) and at T2 (postappliance treatment). Cephalometric values were calculated and assessed to evaluate skeletal, dentoalveolar and soft-tissue changes.Results Sagittal correction of class II malocclusion appeared to be mainly achieved by dentoalveolar changes in the PowerScope group. The FFRD was able to induce both skeletal and dentoalveolar changes. A favorable influence on facial convexity was achieved by both groups. A significant increase in upper pharynx and lower pharynx dimension was seen in the PowerScope group. A statistically significant decrease in upper lip protrusion, increase in lower lip protrusion, increased nasolabial angle, and decrease in inferior labial sulcus were noted in both the groups. Lower incisors proclined more in the PowerScope group.Conclusion Both appliances were effective in correcting class II malocclusion. Forsus had more skeletal effects on the mandible, whereas PowerScope had less skeletal effects on the mandible and more dentoalveolar effects, contributing to class II correction. Both groups showed a significant improvement in soft-tissue profile. PowerScope group showed a significant increase in airway dimensions.
Keywords: retrognathic mandible; skeletal class II malocclusion; Forsus appliance; PowerScope appliance